2012
DOI: 10.1179/1362171812y.0000000010
|View full text |Cite
|
Sign up to set email alerts
|

Linear friction welding of aluminium to copper

Abstract: The joining of dissimilar materials is attaining increasing importance as there is a drive to utilise hybrid structures and reduce the weight or cost of products. The present work therefore studied the linear friction welding of commercially pure grades of aluminium to copper (AA 1050 to C101) for potential power transmission applications. Results showed that welds with very good mechanical and electrical properties can be produced. The weld microstructure was analysed using optical microscopy, backscattered s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…24) For a sound linear friction welding of aluminum to copper of commercially pure grades (AA 1050 to C101) with a weld interface of 50 mm © 12 mm under the condition of 75 MPa friction/forge pressure, 50 Hz frequency, 2 mm oscillation amplitude and 2 mm burn-off distance, a large amount of copper particles and thin intermetallic (CuAl 2 phase) films around these Cu particles were incorporated into weak Al over 100 µm wide strip region, while the thickness of IMC layer at the weld line was calculated to be only 0.7 µm. 25) In linear friction welding of Cu/6063Al of 13 mm © 26 mm area to be welded, the Al and Cu remained contact but distinct, and Cu particles were entrained in the thermo-mechanically affected zone (TMAZ) on 6063Al side, especially for lower power input for relatively long friction time. 26) In contrast to the mixing layer or turbulent zones mainly consisting of Cu particle and deformed Al matrix formed by very high pressure (40³75 MPa) in general rotary and linear friction welded joint, the continuous layer-like morphology of interfacial microstructure formed in the Al/Cu USW joint suggested that the layer-shaped interfacial phase should be finally formed by an surficial alloying activated by high shear deformation rate (and/or degree) under ultrasonic slipping at lower temperature (called ultrasonic mechanical alloying), rather than only or major mechanical mixing.…”
Section: Resultsmentioning
confidence: 99%
“…24) For a sound linear friction welding of aluminum to copper of commercially pure grades (AA 1050 to C101) with a weld interface of 50 mm © 12 mm under the condition of 75 MPa friction/forge pressure, 50 Hz frequency, 2 mm oscillation amplitude and 2 mm burn-off distance, a large amount of copper particles and thin intermetallic (CuAl 2 phase) films around these Cu particles were incorporated into weak Al over 100 µm wide strip region, while the thickness of IMC layer at the weld line was calculated to be only 0.7 µm. 25) In linear friction welding of Cu/6063Al of 13 mm © 26 mm area to be welded, the Al and Cu remained contact but distinct, and Cu particles were entrained in the thermo-mechanically affected zone (TMAZ) on 6063Al side, especially for lower power input for relatively long friction time. 26) In contrast to the mixing layer or turbulent zones mainly consisting of Cu particle and deformed Al matrix formed by very high pressure (40³75 MPa) in general rotary and linear friction welded joint, the continuous layer-like morphology of interfacial microstructure formed in the Al/Cu USW joint suggested that the layer-shaped interfacial phase should be finally formed by an surficial alloying activated by high shear deformation rate (and/or degree) under ultrasonic slipping at lower temperature (called ultrasonic mechanical alloying), rather than only or major mechanical mixing.…”
Section: Resultsmentioning
confidence: 99%
“…Dependent on the process control, IMC formation can be minimized to a total thickness of maximum 5-10 µm. Bhamji et al [26] even reached 0.7 µm in sound welds, presumably by reaching the eutectic temperature and pressing out the formed composite melt between solid Al and Cu.…”
Section: Introductionmentioning
confidence: 96%
“…Typical solidification defects, such as pores, pinholes, shrinkage cracks, segregation, and grain coarsening can be avoided by the absence of a liquid phase during LFW. Therefore, LFW has been widely used to join a range of materials including steels [7,8], aluminum alloys [9][10][11], aluminum to copper [12] and titanium alloys [5,6,13] with the greatest emphasis on aircraft engine alloys [14]. In fact, one successful application of LFW is the welding of aircraft engine blisks with titanium alloys.…”
Section: Introductionmentioning
confidence: 98%